SELF HAND MANIPULATION USING SU-JOK ON HEARTBURN IN ADULTS AT LEMPAKE COMMUNITY HEALTH CENTER - Ziinat Lu'lu', Alvianita; Salsa Billa, Azizah; Puspa Pertiwi, Alda; Fadhilah, Jihan; Marta Dyaksa, Hadyan; Yuliana, Rita; Isnuwardana, Ronny (Mulawarman International Conference on Tropical Public Health, 2025)
Background :Functional dyspepsia affects 24-40% of adults in Indonesia, frequently accompanied by heartburn. At the Lempake Community Health Center in Samarinda, heartburn are the third most common complaint in outpatient clinic, 765 reported cases between January and August 2024. Complaints of heartburn can be self-managed using hand manipulation through Su-Jok therapy. Objective : This study aimed to evaluate the effectiveness of Su-Jok complementary intervention for heartburn relief in adults. Research Methods/ Implementation Methods : We employed a non-randomized trial design without control group from patient visiting the clinic. Data was collected through structured interviews using questionnaire and Numerical Rating Scale (NRS) of pain before and after intervention to patients experiencing non-complicated heartburn. Results : The study involved 20 respondents aged 19 to 55, with 75% being female. Results were analyzed using the Wilcoxon test, revealing a statistically significant difference in NRS before and after the application of Su-Jok, with p-value <0.001. Conclusion/Lesson Learned : These findings indicate that hand manipulation through Su-Jok can significantly alleviate non-complicated heartburn symptoms. Therefore, Su-Jok therapy may be considered a viable initial or complementary treatment option for heartburn, potentially providing relief before patients seek further medical intervention.